11. Study of Cat’s Welfare Kept at Pet Shops in Gajah Mada Mal Central Jakarta - Putri Aisyah Hanifah; Mulyadi Adam; Roslizawaty Roslizawaty; Abdullah Hamzah; Erdiansyah Rahmi; T. Armansyah TR (Universitas Syiah Kuala, 2020)
The aim of this study was to find out correlation between cat’s welfare and caring management in a number of cats kept at pet shops in Gajah Mada mal Central Jakarta, from January to February 2016. This study used a questionnaire with ratings based on five aspects of animal welfare (freedom from hunger and thirst, freedom from discomfort, freedom from pain, injury, and disease, freedom from fear and distress, and freedom to express normal behavior) and through direct observation. Data was analyzed by Correlation Test Chi Square with 95% confidence interval. The result shows that there is a significant correlation (P0,05) in freedom from hunger and thirst with freedom from fear and distress aspects, and there is no correlation (P0,05) between caring management and animal welfare standart in freedom from pain, injury, and disease aspects, freedom from discomfort aspect, and freedom to express normal behavior with caring management aspects.